If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(-42x + 48) = 15(-8x + 244) Reorder the terms: 15(48 + -42x) = 15(-8x + 244) (48 * 15 + -42x * 15) = 15(-8x + 244) (720 + -630x) = 15(-8x + 244) Reorder the terms: 720 + -630x = 15(244 + -8x) 720 + -630x = (244 * 15 + -8x * 15) 720 + -630x = (3660 + -120x) Solving 720 + -630x = 3660 + -120x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '120x' to each side of the equation. 720 + -630x + 120x = 3660 + -120x + 120x Combine like terms: -630x + 120x = -510x 720 + -510x = 3660 + -120x + 120x Combine like terms: -120x + 120x = 0 720 + -510x = 3660 + 0 720 + -510x = 3660 Add '-720' to each side of the equation. 720 + -720 + -510x = 3660 + -720 Combine like terms: 720 + -720 = 0 0 + -510x = 3660 + -720 -510x = 3660 + -720 Combine like terms: 3660 + -720 = 2940 -510x = 2940 Divide each side by '-510'. x = -5.764705882 Simplifying x = -5.764705882
| 3n+11=25 | | r-21=137 | | (18+9x^2-20x^4-6x)/(-4x^2+5) | | -4/5x+1=-13 | | y/-12=72 | | x-5.6=-1.7 | | h(x)=2(x-7) | | a-5/6=-11/3 | | 9x^3+3x^2-6x=0 | | X(x-2b)-9a-15b=0 | | 6X^2-18X+9=0 | | 5y-3.2+4.7y-4.5y-3= | | (3x+7y)-(x+12y)=0 | | 2x-4(x-3)=-8+4x-16 | | a-5/6=-32/3 | | 15y+15+6= | | Z+2/1.2=-5 | | -(6x+1)-(-5x-3)=1 | | f(x)=10x-1+x(-5x-6) | | -8x-8y=-16 | | 3n+17=19 | | x+10+3x-19=111 | | 12-a^2=40 | | x-24=12-2x | | -20*3/2 | | 5x+82=192 | | x^2+6x+8y-31=0 | | 21=5/9(f-32) | | y-.4y=3500 | | y=8x^2+7x+12 | | 15x+13-12x-17= | | 7r-2=13+4r |